Earwax: A clue to discover fluoroacetate intoxication in cattle. (October 2017) - Shokry, Engy; dos Santos, Fabrício Carrião; da Cunha, Paulo Henrique Jorge; Fioravanti, Maria Clorinda Soares; Noronha Filho, Antônio Dionísio Feitosa; Pereira, Naiara Zedes; Antoniosi Filho, Nelson Roberto
Abstract: An innovative method was developed to detect fluoroacetate poisoning in cattle by headspace/gas chromatographic analysis of earwax samples of intoxicated cattle. Samples were collected from 2 groups of cattle subjected to induced fluoroacetate intoxication, each group receiving a different dose of acetamide (antidote). Monofluoroacetic acid was detected in samples of intoxicated cattle in concentrations inversely proportional to the dose of acetamide. Thus, earwax analysis represents a successful approach for detection and monitoring of fluoroacetate poisoning. Graphical abstract: Highlights: The method employs HS/GC-MS analysis of earwax for detecting exposure to fluoroacetate poisoning in cattle. It involves noninvasive, rapid, and easy sample collection and no extraction, pretreatment or derivatization procedures. It offers an easy solution for the difficulty in diagnosis of fluoroacetate poisoning mistaken for many other differentials. It can be applied in diagnosis of sudden death due to fluoroacetate poisoning and in survivors to detect past exposure. It can help to minimize health risks to cattle with sublethal fluoroacetate exposure and secondary intoxication to feeders.